Enteroparasitosis en niños desnutridos graves de un hospital de la ciudad de Maracaibo, Venezuela - Maldonado I Adriana; Bracho M Ángela; Rivero-Rodríguez Zulbey; Atencio Teresa; de Molano Nelly; Acurero O Ellen; Calchi L Marinella; Villalobos P Rafael (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Abstract: To compare the prevalence of intestinal parasites in children with severe malnutrition in the Nutritional Recovery Unit at the Chiquinquirá Hospital of Maracaibo, State of Zulia, with eutrophic children attending consult for healthy children at the same hospital, stool examinations were performed for 50 seriously malnourished children and 50 eutrophic children by direct examination, using the concentration technique (Ritchie) and Ziehl Neelsen. Among the protozoa, Cryptosporidium sp. ranked first, with 14% in the group of severely malnourished and Giardia lamblia in 20% of the eutrophic children. Of the identified helminths, Trichuris trichiura prevailed, with 12% in the malnourished group, while Ascaris lumbricoides took first place with 8% in the eutrophic group. No statistically significant difference was found between the prevalence of parasites in general with age, sex or malnutrition, or between polyparasitism versus monoparasitism. The extent to which malnutrition and intestinal parasites relate is difficult to clarify, since malnutrition is a multifactorial condition that depends on the parasite species present, intensity of the parasitosis, immunologic and genetic characteristics of the host, the socio-economic environment in which the individual develops and other factors. Resumen: Para comparar la prevalencia de enteroparásitos en niños con desnutrición severa de la Unidad de Recuperación Nutricional del Hospital Chiquinquirá de Maracaibo, Estado Zulia, con niños eutróficos que asisten a la consulta de niños sanos del mismo hospital; se realizó un examen coproparasitológico a 50 niños desnutridos graves y 50 niños eutróficos, mediante examen directo; técnica de concentración (Ritchie) y coloración de Ziehl Neelsen. Entre los protozoarios, Cryptosporidium sp. ocupó el primer lugar con un 14% en el grupo de los desnutridos graves y Giardia lamblia en los eutróficos con un 20%. De los helmintos identificados, Trichuruis trichiura prevaleció con 12% en los desnutridos, mientras Ascaris lumbricoides en los eutróficos ocupó el primer lugar con un 8%. No se encontró diferencia estadísticamente significativa entre la prevalencia de parásitos en general con la edad, el sexo o la desnutrición, ni entre poliparasitismo versus monoparasitismo. La medida en que se relacionan la desnutrición y las parasitosis intestinales es difícil de esclarecer, al ser la desnutrición una condición multifactorial ya que depende de la especie parasitaria presente, la intensidad de la parasitosis, las características inmunológicas y genéticas del hospedero, del medio socioeconómico en el que se desenvuelva el individuo, entre otros factores.